INTEGRASI LITERASI DALAM EVALUASI PEMBELAJARAN: TANTANGAN DAN PELUANG PENDIDIKAN DI ERA DIGITAL - Harjon, Losianus; Yanto Nahak, Antonius Redy; Primus Bala Lajar, Theodor Advent; Mite Ajo, Leonardus Roland; Mau, Bonifasius Stefen; Aunsuni, Marianus Dedy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literacy culture is a reflective practice that enables humans to understand life experiences more deeply. Through reading and writing, humans not only record reality but also interpret the meaning of various events experienced in daily life. However, the development of digital technology has changed the way humans acquire knowledge. Information is now readily available through various online media, such as social media, comments, and short text snippets. This situation raises questions about the difference in the quality of understanding between literacy obtained through fast-paced digital media and literacy obtained through the process of reading books in depth. This study aims to analyze the comparison between the practice of reading brief information in digital media and reading books in their entirety in relation to character building and depth of individual understanding. The research method used is a descriptive qualitative approach through a literature study. The results of the study show that digital literacy provides easy access to information, but often results in superficial understanding due to its instant and fragmentary nature. Conversely, reading books allows for a more in-depth reflection process, builds intellectual perseverance, and contributes to the formation of a stronger individual character. Thus, the culture of reading books continues to play an important role in building depth of thought and intellectual identity in the midst of the digital information flow.